THE GENETIC EFFECTS OF COM BIN lNG ABILITIES ON OIL AND PROTEIN CONTENTS IN GOSSYPJUM HIRSVTVM L. SEED (Biological Sciences - PJSIR, 2003)
An eight parent diallel cross data was analysed by following Griffing 's method of genetic analysis, to examine genetic effects of general and specific combining abilities of the parents on cotton seed oil and protein contents. The higher gca:sca mean squares showed , that genes showing additive properties had predominant influence on the inheritance of the characters. The parents having better general combining ability (gca) for the characters, appeared to result in better specific combinations. The nature of the gene's action suggests that further improvement in oil and protein contents  may be achieved by making single plant selections from the F2   population .